2012
DOI: 10.1021/bi301224b
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-Induced Nucleophile Activation in the Guanylyltransferase mRNA Capping Enzyme

Abstract: The messenger RNA guanylyltransferase, or mRNA capping enzyme, co-transcriptionally caps the 5′-end of nascent mRNA with GMP during the second in a set of three enzymatic reactions that result in the formation of an N7-methyl guanosine cap during mRNA maturation. The mRNA capping enzyme is characterized, in part, by a conserved lysine nucleophile that attacks the alpha-phosphorous atom of GTP, forming a lysine-GMP intermediate. Experiments have firmly established that magnesium is required for efficient interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…In the hepatitis delta virus (HDV) ribozyme, which has a similar divalent metal ion requirement under physiological conditions, a pK a shift of similar magnitude (~−4 units) on the 2′-hydroxyl nucleophile induced by Mg 2+ was predicted by 3D-RISM calculations(95). Further, Amaro and co-workers have reported the Mg 2+ -induced pK a shift of lysine K82 in guanylyltransferase mRNA capping enzyme to be −4.2(94) which is very close to the result reported here using a similar TI approach. Rosta and co-workers have also observed that Mg 2+ plays the role of altering pK a in dUTPase which catalyzes phosphate hydrolysis(96, 97).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the hepatitis delta virus (HDV) ribozyme, which has a similar divalent metal ion requirement under physiological conditions, a pK a shift of similar magnitude (~−4 units) on the 2′-hydroxyl nucleophile induced by Mg 2+ was predicted by 3D-RISM calculations(95). Further, Amaro and co-workers have reported the Mg 2+ -induced pK a shift of lysine K82 in guanylyltransferase mRNA capping enzyme to be −4.2(94) which is very close to the result reported here using a similar TI approach. Rosta and co-workers have also observed that Mg 2+ plays the role of altering pK a in dUTPase which catalyzes phosphate hydrolysis(96, 97).…”
Section: Resultssupporting
confidence: 86%
“…The convergence of the TI simulations in terms of the target observable pK a shifts was measured (Fig. 6) and showed that the simulations reached reasonable convergence after 1 ns, which was similar to the timescales investigated in related work(56, 93, 94). Experimental activity-pH profiles indicate that the apparent pK a of the general base in HHR is around 8 in the presence of Mg 2+ (15).…”
Section: Resultssupporting
confidence: 80%
“…These findings suggest that insufficient Mg in the male mgt5 and mgt9 gametophytes led to developmental defects. Magnesium is a mineral element that is important for many functions of living cells including DNA replication and transcription and enzyme activity (Jensen et al, 2000;Batra et al, 2006;Swift et al, 2012). Hence, insufficient Mg in the male gametophyte may affect DNA replication, gene expression and enzyme activity during mitosis and intine formation.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium (Mg) is a divalent metal cation that is important for numerous biological processes and cellular functions in living cells, including DNA replication and posttranscriptional processing (Batra et al, 2006;Swift et al, 2012). Magnesium uptake and its dynamic balance in the cell rely on Mg transporters.…”
Section: Introductionmentioning
confidence: 99%
“…18 The reaction is held in the presence of the divalent metal cation Mg 2+ , which minimizes the charge repulsion between phosphate groups, favoring nucleophile activation. 19,20 Moreover, two positively charged residues polarize these groups, increasing the nucleophilic nature of the oxygen attacking the phosphor atom. 21,22 AGPase follows a sequential ordered bi-bi mechanism with ATP binding first, followed by G1P and by the ordered release of PPi and ADPglucose.…”
Section: Introductionmentioning
confidence: 99%